(untitled) (Research, Society and Development, 2024)
Perianal fistula is a conical, progressive, and painful inflammatory lesion that presents with ulceration in the anal and perianal regions. Current treatments consist of cleaning the area and analgesics or a surgical approach. Currently, stem cell therapy has been used successfully in the treatment of various diseases that affect small and large animals. The aim of this study was to evaluate the safety and efficacy of multipotent adult progenitor cell therapy in the treatment of perianal fistula in dogs. In the present study, twelve dogs were selected that had a perianal fistula for at least six months, and were refractory to treatment with cyclosporine A. The patients underwent cell transplantation with allogeneic stem cells to determine their safety and therapeutic efficacy. The results obtained demonstrated that this new methodology can result in the recovery of patients’ quality of life.